2021
DOI: 10.3390/ijerph18126349
|View full text |Cite
|
Sign up to set email alerts
|

Safe Sexual Behavior Intentions among College Students: The Construction of an Extended Theory of Planned Behavior

Abstract: Sexual health education is an essential part of quality-oriented education for college students. It aims to help these students to acquire knowledge of sexual physiology, sexual psychology, and sexual social norms that is consistent with the maturity of the students. Along with college students’attitudes toward sex, their perceptions regarding sexual behavior have also undergone profound changes. The importance of safe sexual behavior, sexual taboos, and sexual autonomy are gaining increasing attention as Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…The route coefficients of groups divided by sex and major were compared. Gender and major are two elements that influence behavior, according to existing research (Potard et al, 2017;Morales et al, 2018;Lin et al, 2021b). As a result, the main classification factors in this study were gender and major.In terms of sex (Table 5), there is a significant difference in the p-value of the subject norm on employment and entrepreneurial intention between the two groups, among which the male (0.016) is less than the female (0.071).…”
Section: Structural Modelsupporting
confidence: 51%
See 1 more Smart Citation
“…The route coefficients of groups divided by sex and major were compared. Gender and major are two elements that influence behavior, according to existing research (Potard et al, 2017;Morales et al, 2018;Lin et al, 2021b). As a result, the main classification factors in this study were gender and major.In terms of sex (Table 5), there is a significant difference in the p-value of the subject norm on employment and entrepreneurial intention between the two groups, among which the male (0.016) is less than the female (0.071).…”
Section: Structural Modelsupporting
confidence: 51%
“…The route coefficients of groups divided by sex and major were compared. Gender and major are two elements that influence behavior, according to existing research ( Potard et al, 2017 ; Morales et al, 2018 ; Lin et al, 2021b ). As a result, the main classification factors in this study were gender and major.…”
Section: Resultsmentioning
confidence: 99%
“…College students are a large and special group, and their involvement in unsafe sexual behaviors exposes them to various risks. A study revealed that less than 30% of college students in mainland China used condoms when having sex for the first time ( Lin et al, 2021b ). More than 6 million abortions are performed annually on women aged < 25 years, and the proportion of women with multiple partners has reached 48.9% ( Liu, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…College students who have sex do not take appropriate protective measures because they fear that doing so reduces the pleasure of sexual intercourse and may even threaten the development of their relationships ( Strachman and Impett, 2009 ). Moreover, women under the age of 25 account for almost half of all abortions performed in China annually, and most of these abortions are performed on college students ( Lin et al, 2021b ). Therefore, to reduce the social problems caused by unsafe sex among college students, Chinese college students’ understanding of safe sex must first be investigated, and the relevant data that are collected may help to popularize sex education in colleges and universities in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation